Merajut Industri Kreatif di Panti Asuhan Mawaddah Warohmah melalui Pelatihan Seni Patchwork dan Lace - Yekti Sri Rahayu; Erna Atiwi Jaya Esti (Jurnal Pemberdayaan Masyarakat, 2021)
Mawaddah Warohmah Orphanage Malang City is the social service institutions that accommodates orphans and poor people from various regions. The skill development of the productive age orphanage children has not been maximally obtained. This program aims to improve the skills of orphans and poor people under the guidance of the orphanage through the development of creative industries that have the opportunity to become home-scale businesses. The group participation approach method in this program involves orphans and poor people under the guidance of the Orphanage actively in training and mentoring for creative classes "patchwork and lace" as well as entrepreneurship counseling and business planning. The results of the program implementation showed that 80% of orphans and poor people assisted by the Mawadah Warohmah orphanage were able to attend the training well and were shown to have skills in patchwork and lacee arts. Their craftsmanship from patchwork is demonstrated by handmade products in the form of blankets of various designs and motif modifications. Meanwhile, their works from lacee art training include handbags, scarves, tablecloths, brooches, bags, shoes and babies. clothes, and wallets. The intensive mentoring program through an alliance between the orphanage (the first partner) and Toko Jaya (the second partner) is able to support the development of creative businesses through the marketing of products produced from orphaned children and the underprivileged